Conditions during expander processing of soybean meal and raw soybeans affect nutrient digestibility in finishing pigs - Traylor, S.L.; Hines, Robert H.; Amornthewaphat, N.; Johnson, S.L.; Sorrell, P.; Hancock, Joe D.; Behnke, Keith C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Expander processing improved nutrient digestibility in diets with soybean meal and raw soybeans. Furthermore, with 600 psi cone pressure (20 k Wh/tonon ofspecific energy input), the diets with raw soybeans had equal or greater digestibility of nutrients compared to the soybean meal-based control diet.
Keywords: Swine; Expander; Soybean; Digestibility; Finishing pigs